(untitled) (Jurnal Akuntansi dan Manajemen STIE Karya, 2026)
Strengthening the economic resilience of communities around conservation areas requires marketing systems that expand market access while ensuring equitable value distribution. This study analysed the marketing systems of micro, small, and medium enterprise (MSME) products managed by Forest Farmer Groups (KTH), identified opportunities and constraints affecting competitiveness, and formulated strategies to strengthen marketing performance in East Manggarai and Ngada Regencies, East Nusa Tenggara, Indonesia. A mixed-methods approach with a descriptive-analytical design was employed. Primary data were collected through structured interviews using a 37-item questionnaire administered to 40 respondents from 10 active KTH groups. The commodities analysed included local food products, traditional woven textiles, and seaweed. Quantitative analysis covered marketing channels, margins, farmer’s share, marketing costs, and efficiency, while qualitative analysis examined pricing, institutional arrangements, promotion, business constraints, and strategic factors using SWOT analysis. Results showed substantial differences in marketing performance. Local food products achieved the highest average farmer’s share (85.8%), followed by woven textiles (64.3%) and seaweed (52.8%). Higher shares for food products were associated with direct-to-consumer channels, whereas woven-textile and seaweed producers remained dependent on intermediaries. None of the groups had formal written contracts with buyers, certification remained limited, and social media use was low. The study concludes that stronger marketing performance requires shorter supply chains, cost-based pricing, product standardisation and certification, digital marketing, collective marketing institutions, and direct partnerships with premium buyers and processors.